Pedagogical Philosophies of Teacher Educators in the Philippines: Implications for Teacher Quality - Muthoifin Muthoifin; Mariam Elbann; Amirkhon Yorov (JURNAL PEDAGOGY, 2026)
This study aimed to examine the pedagogical philosophies of teacher educators in the Ilocos Region, Philippines, to understand their implications for teacher quality amid national reforms. The research sought to identify espoused philosophies, categorize them into distinct profiles, and analyze their variation across educator and institutional characteristics. A convergent parallel mixed-methods design was employed to analyze survey data from 391 teacher educators. Thematic analysis of open-ended responses was combined with quantitative profiling and cross-tabulations to map the pedagogical landscape. The results revealed a dominant model of "Pragmatic Constructivism with Cultural Grounding," emphasizing theory-practice integration (33.7%), experiential learning (31.8%), and authentic contexts (23.4%). An eclectic approach was the most common profile (57.3%). A significant "experience paradox" emerged: pedagogical sophistication declines as teaching experience increases, while no significant differences were found across institutional types. The study concludes that although teacher educators' philosophies align with evidence-based practices, the experience paradox poses a significant threat to the sustained implementation of pedagogical innovation. Improving teacher quality requires intentional institutional strategies, such as intergenerational learning communities and support for novice-led innovation, to ensure progressive pedagogies are maintained and integrated system-wide.